Food and feeding habits of Channa punctatus from Kaigaon Toka Dist. Aurangabad (M.S.) in relation to biochemical studies - Sonawane, Smita; Gedam, Ajit; Anand, Sunil; Pawar, Sandhya (Journal of Experimental Sciences, 2013)
The research presents food and feeding habits of Channa punctatus (Bloch, 1793) in relation to biochemical studies from Kaigaon Toka Dist. Aurangabad (M.S.). Feeding habits, seasonal diet variation of Channa punctatus were investigated through stomach content analysis during December 2007 to November 2009. The diet showed significant seasonal patterns and was dominated by crustaceans, followed by insects, molluscs, fishes and least by plant material thus reflecting its carnivorous nature. In biochemical studies various digestive enzymes glycosidases, proteases and lipases were detected in the different regions of gut.